Teaching Strategies of Translation Subject Using Variants Online Translators - Ika Oktaria Cahyaningrum Yunita Widiyantari (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to develop learning strategies on Translation subject using variants onlinetranslator. Increasing development of learning strategies is needed because of the rapiddevelopment of digital era technology. Another purpose of this research is to develop learningstrategies and discuss in detail about variations online translator. Furthermore, students are able tomeasure quality of translation products.Keynote: (development learning strategies, translation method, online translator)